(3TQa GdWGdH aj CSfi GdeWGdHs - (3GHf bfaP , CHh GdYHGS CMeO Hf GdMSjf Hf Ydj Hf GdNWjH Hf bfaP GdbSfWjfj, GHf GdNWjH, GHf bfaP,J (B810 (3g` s
(3ChdgG (B:s
(3GPcQ ai gPG GdcJGH eG MVQfi ef hajGJ GdUMGHI hGdYdeGA hGdeMOKjf hGdeDdajf hQJHJg Ydi GdeFjf HhLg de CSHb Edjg s
(3BNQgG (B:s
(3hGddg Gdehab , dGQH ZjQg hdGeYHhO ShGg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B80 (3C (B- (3U(B103 (3Hs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B117 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B205s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B241 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B341 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B255 s
Keywords: (3GdJGQjNs